A case study : perceptions and experiences on artificial intelligence in financial administration - Punnala, Santeri (2021)
Artificial intelligence is rapidly becoming a technology that has the potential to create significant competitive advantage for companies in different sectors of business, and financial administration is not an exception. While there have been some studies on AI from the ac-counting perspective, research on the human perspective on AI in financial administration (or any other sector of accounting) is non-existent. This master’s thesis has been produced to fill the gap between technical AI research and subjective human perceptions. Research on the subject is especially important, since perceptions of financial administration personnel, especially those in management or executive positions have major impacts in how their organizations use AI, regardless of if they are true or accurate. The research of this thesis was conducted as a case study together with Snowfox Oy, that has since 2018 been offering one of the first AI-based solution for purchase invoice management in the world. The research material was collected through half structured thematic interviews of customers of the case company and the research material was analyzed with qualitative methods. Based on the results, AI is rapidly becoming a part of financial administration and other accounting processes, but there are clear challenges ahead in this trajectory. Most of these challenges seem to be related to human factors and the general understanding of AI-based technologies. This thesis was able to identify a significant number of motivators for using AI in financial administration, main challenges organizations face when implementing AI into their processes and a significant amount clearly defined and re-occurring benefits AI-usage has brought into financial administration organizations, such as better understanding of an organization's own processes. In the big picture financial administration personnel seem to have an overall positive feeling about AI, but the nature of the accounting field causes certain challenges in implementing the technology. The possibilities for AI utilization seem to appear mainly disorganized for professionals of the field, but the general potential of the technology has been recognized. The need for more education on the subject also came up in the research mate-rial, which correlates well with existing research.